Comparison of mineral content of bottled spring and mineral waters marketed in Turkey - Turhan, Şeref; Kurnaz, Aslı; Hançerlioğulları, Aybaba (Turkish Science and Technology Publishing (TURSTEP), 2021)
Drinking water is the most indispensable substance for humans. Bottled drinking waters are preferred over tap water with the belief that they are more nutritious, better quality, more delicious and safe in terms of health. Therefore, the Turkish bottled (spring and mineral) water market has experienced a continuous growth since 2003, as in the whole world. This study focuses on comparing the common mineral cation calcium (Ca2+), magnesium (Mg2+) and sodium (Na+) content of twenty one popular bottled spring and mineral water brands marketed in Turkey by using an inductively coupled plasma optical emission spectrometry (ICP-OES). The average concentrations of Ca, Mg and Na analyzed in bottled spring and mineral water samples were found as 14.9, 24.1 and 8.2 mg/L and 147.9, 44.3 and 117.3 mg/L, respectively. This comparison confirms that bottled natural mineral water has better quality in terms of major nutrient minerals than bottled natural spring waters.
Keywords: calcium; bottled spring water; major nutrient; S; Agriculture (General); Agriculture; magnesium; bottled mineral water; sodium; S1-972; 6. Clean water